Therapeutic endobronchial resection of a benign tumor in a patient with cystic fibrosis - Gohy, Sophie (Clin Case Rep, 2019)
This report highlights the usefulness of bronchoscopy in case of recurrent pneumonia with the same localization even in CF patients where the presence of bronchiectasis as promoting factor of infections could delay the diagnosis.